A carbon-based adsorption electrocatalytic membrane and its preparation method and application

CN118978231BActive Publication Date: 2025-02-18江苏环保产业技术研究院股份公司 +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411263107.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-18
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing electrocatalytic films have problems with low oxygen evolution potential and limited adsorption performance in pollutant removal, which affects its pollutant removal efficiency.

Method used

A carbon-based adsorption electrocatalytic film is prepared by combining materials such as titanium oxide, activated carbon, carbon nanotubes and organic binders. The film is formed by pressing and sintering processes, which enhances the conductivity and pore size controllability of the film and improves adsorption and electrocatalytic oxidation properties.

Benefits of technology

Efficient pollutant removal is achieved, especially in the treatment of low-pollution organic wastewater, which can significantly improve the pollutant removal efficiency and further improve the degradation efficiency in the micro-nano space.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005037242300000081
    Figure BDA0005037242300000081
Patent Text Reader

Abstract

The present invention belongs to the technical field of wastewater treatment, and provides a carbon-based adsorption electrocatalytic membrane and a preparation method and application thereof. The method comprises the following steps: mixing titania, an organic binder and water to obtain titania sol a; impregnating activated carbon in titania sol a to obtain Ti4O7 / C powder; mixing titania, Ti4O7 / C powder, carbon nanotubes and an organic binder to obtain a membrane-based raw material; pressing the membrane-based raw material to obtain a base membrane; mixing titania, an organic binder and water to obtain titania sol b; loading titania sol b on the surface of the base membrane to obtain an original membrane; sintering the original membrane to obtain a carbon-based adsorption electrocatalytic membrane. The carbon-based adsorption electrocatalytic membrane prepared by the present invention has separation, adsorption and electrocatalytic oxidation properties at the same time, and can greatly improve the removal efficiency of pollutants in the deep treatment of low-pollution organic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wastewater treatment, and in particular to a carbon-based adsorption electrocatalytic membrane and a preparation method and application thereof. Background Art

[0002] Electrocatalytic membranes combine electrochemical oxidation and membrane separation technologies, and have broad application prospects in the field of deep treatment of low-pollution wastewater. They combine electrochemical oxidation with membrane separation, effectively solving the problems of high energy consumption and membrane pollution in the electrochemical oxidation process, and achieving synergistic efficiency. Adsorption technology is a fast and effective pollutant enrichment and removal technology. Coupling electrocatalytic membranes with adsorption technology to develop a membrane material that integrates separation, adsorption and electrocatalytic oxidation technologies can further improve the pollutant removal performance of electrocatalytic membranes, and achieve the effect of enriching and oxidatively degrading small molecule pollutants when they pass through the membrane.

[0003] Chinese patent CN107051218A discloses a carbon membrane with triple functions of adsorption / electrocatalysis / membrane separation and its preparation method, using porous carbon, conductive agent (graphite, activated carbon fiber, carbon black, conductive carbon nanotubes and graphene) and catalyst (titanium dioxide, nickel oxide, cobalt oxide, zinc oxide, etc.) as raw materials to prepare adsorption electrocatalytic membrane, achieving the adsorption, electrocatalysis and membrane separation performance of the membrane, and can quickly achieve the separation and degradation of pollutants, but the oxygen evolution potential of the catalyst is generally low, which will have an adverse effect on the current efficiency. Chinese patent CN116730442A discloses a multifunctional hollow fiber electrocatalytic membrane and its preparation method, which loads a layer of sub-titanium oxide-carbon composite catalytic layer on the surface of the titanium-based membrane, achieving the adsorption, catalytic oxidation and separation functions of the membrane, and is used for the purification of micro-polluted water. However, it uses carbon materials produced by pyrolysis of organic ligands to achieve the adsorption performance of the electrocatalytic membrane, and the adsorption performance is limited.

[0004] Therefore, it is of great significance to provide an adsorption electrocatalytic membrane with high oxygen evolution potential, good adsorption performance and excellent comprehensive performance. Summary of the invention

[0005] The purpose of the present invention is to provide a carbon-based adsorption electrocatalytic membrane and a preparation method and application thereof, so as to further improve the pollutant removal performance of the electrocatalytic membrane, thereby being suitable for deep treatment of organic wastewater in different industries.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a carbon-based adsorption electrocatalytic membrane, comprising the following steps:

[0008] (1) mixing titanium oxide, an organic binder and water to obtain a titanium oxide sol a; impregnating activated carbon into the titanium oxide sol a to obtain Ti4O7 / C powder; mixing titanium oxide, Ti4O7 / C powder, carbon nanotubes and an organic binder to obtain a film base material; pressing the film base material to obtain a base film;

[0009] (2) mixing titanium dioxide, an organic binder and water to obtain a titanium dioxide sol b;

[0010] (3) loading the titanium oxide sol b on the surface of the base film to obtain an original film; sintering the original film to obtain the carbon-based adsorption electrocatalytic film;

[0011] There is no particular order in which steps (1) and (2) are performed.

[0012] Preferably, in step (1), when preparing titania sol a, the particle size of titania is 5 to 10 nm, the organic binder includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, the mass ratio of titania to organic binder is 1:4 to 5, and the mass fraction of titania in titania sol a is 10 to 15%.

[0013] Preferably, in step (1), when preparing Ti4O7 / C powder, the particle size of the activated carbon is 50-100 μm, the negative pressure value of the impregnation is 0.03-0.06 MPa, the number of impregnations is 1-5 times, and the time of each impregnation is independently 8-12 hours.

[0014] Preferably, in step (1), when preparing the membrane base material, the particle size of titanium oxide is 50-100 nm, the length of carbon nanotubes is 10-15 μm, the organic binder is polyvinyl alcohol, and the molecular weight of polyvinyl alcohol is 2*10 5 ~4*10 5 Da; the mass ratio of titanium oxide, Ti4O7 / C powder and carbon nanotubes is 3-5:14-16:0.5-1.5; the mass fraction of the organic binder in the film base material is 5-10%;

[0015] The pressing pressure in step (1) is 20 to 30 MPa.

[0016] Preferably, the particle size of the titanium oxide in step (2) is 10 to 30 nm, the organic binder includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, the mass ratio of titanium oxide to the organic binder is 1:2.5 to 3.5, and the mass fraction of titanium oxide in the titanium oxide sol b is 15 to 25%.

[0017] Preferably, the loading method in step (3) is immersion pulling, the number of immersion pulling is 1 to 3 times, and the time of each immersion pulling is independently 60 to 90 seconds.

[0018] Preferably, the sintering atmosphere in step (3) is hydrogen, the flow rate of hydrogen is 90-120 mL / min, the sintering temperature is 1000-1350° C., and the sintering time is 6-8 h.

[0019] The present invention also provides a carbon-based adsorption electro-catalytic membrane prepared by the method for preparing the carbon-based adsorption electro-catalytic membrane.

[0020] The present invention also provides application of the carbon-based adsorption electrocatalytic membrane in wastewater treatment.

[0021] The beneficial effects of the present invention are:

[0022] The invention provides a method for preparing a carbon-based adsorption electrocatalytic membrane, comprising the following steps: mixing titania, an organic binder and water to obtain titania sol a; impregnating activated carbon into the titania sol a to obtain Ti4O7 / C powder; mixing titania, Ti4O7 / C powder, carbon nanotubes and an organic binder to obtain a membrane-based raw material; pressing the membrane-based raw material to obtain a base membrane; mixing titania, an organic binder and water to obtain titania sol b; loading the titania sol b on the surface of the base membrane to obtain an original membrane; and sintering the original membrane to obtain a carbon-based adsorption electrocatalytic membrane. The present invention combines the adsorption performance of carbon materials and the high conductivity of titanium oxide, prepares Ti4O7 / C adsorption conductive particles by modifying carbon materials, realizes controllable base membrane pore size by regulating Ti4O7 / C powder and Ti4O7 powder particle size, adopts carbon nanotubes to enhance the connection strength and conductivity between base membrane raw material particles, and loads a dense pore conductive separation layer on the surface of the base membrane to form a heterogeneous carbon-based adsorption electrocatalytic membrane, thereby reducing the pollution of pollutants to the base membrane. The carbon-based adsorption electrocatalytic membrane prepared by the present invention has separation, adsorption and electrocatalytic oxidation performance at the same time, and can greatly improve the removal efficiency of pollutants in the deep treatment of low-pollution organic wastewater. When small molecular pollutants pass through the membrane, they can be enriched and degraded in the membrane body; in addition, the degradation efficiency of pollutants can be further improved in the micro-nano space, thereby improving the removal efficiency of pollutants. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing a carbon-based adsorption electrocatalytic membrane, comprising the following steps:

[0024] (1) mixing titanium oxide, an organic binder and water to obtain a titanium oxide sol a; impregnating activated carbon into the titanium oxide sol a to obtain Ti4O7 / C powder; mixing titanium oxide, Ti4O7 / C powder, carbon nanotubes and an organic binder to obtain a film base material; pressing the film base material to obtain a base film;

[0025] (2) mixing titanium dioxide, an organic binder and water to obtain a titanium dioxide sol b;

[0026] (3) loading the titanium oxide sol b on the surface of the base film to obtain an original film; sintering the original film to obtain the carbon-based adsorption electrocatalytic film;

[0027] There is no particular order in which steps (1) and (2) are performed.

[0028] In the present invention, in step (1), when preparing titania sol a, the particle size of titania is preferably 5-10 nm, more preferably 6-9 nm, and more preferably 7-8 nm; the organic binder preferably includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, and the mass ratio of titania to organic binder is preferably 1:4-5, more preferably 1:4.3-4.7, and more preferably 1:4.5-4.6; the mass fraction of titania in titania sol a is preferably 10-15%, more preferably 11-14%, and more preferably 12-13%.

[0029] In the present invention, in step (1), when preparing Ti4O7 / C powder, the activated carbon is preferably wood activated carbon or coconut shell activated carbon, and the particle size of the activated carbon is preferably 50-100 μm, more preferably 60-90 μm, and more preferably 70-80 μm; the negative pressure value of the impregnation is preferably 0.03-0.06 MPa, more preferably 0.035-0.055 MPa, and more preferably 0.04-0.05 MPa; during impregnation, the amount of activated carbon and titania sol a is determined by conventional technical means in the art to ensure that the activated carbon is completely immersed; the number of impregnations is preferably 1-5 times, more preferably 2-4 times, and more preferably 3 times; the time of each impregnation is independently preferably 8-12 hours, more preferably 9-11 hours, and more preferably 9.5-10 hours.

[0030] In the present invention, in step (1), when preparing Ti4O7 / C powder, after each impregnation, it is dried under vacuum conditions, and then the next impregnation is carried out, and then it is dried again, and the impregnation-drying process is repeated to finally obtain Ti4O7 / C powder; the drying temperature is preferably 100-120°C, more preferably 105-115°C, and more preferably 110°C; the drying time is preferably 12-24h, more preferably 15-21h, and more preferably 16-18h.

[0031] In the present invention, in step (1), when preparing the membrane base material, the particle size of titanium oxide is preferably 50 to 100 nm, more preferably 60 to 90 nm, and more preferably 70 to 80 nm; the length of the carbon nanotube is preferably 10 to 15 μm, more preferably 11 to 14 μm, and more preferably 12 to 13 μm; the organic binder is preferably polyvinyl alcohol, and the molecular weight of the polyvinyl alcohol is preferably 2*10 5 ~4*10 5 Da, more preferably 2.5*10 5 ~3.5*10 5 Da, more preferably 3*10 5 Da; the mass ratio of titanium dioxide, Ti4O7 / C powder and carbon nanotubes is preferably 3-5:14-16:0.5-1.5, further preferably 3.5-4.5:14.5-15.5:0.7-1.3, and more preferably 4:15:1; the mass fraction of the organic binder in the film base raw material is preferably 5-10%, further preferably 6-9%, and more preferably 7-8%.

[0032] In the present invention, the pressing mold type in step (1) is preferably a plate type and a tube type; the pressing pressure is preferably 20 to 30 MPa, more preferably 22 to 28 MPa, and more preferably 25 to 26 MPa; after pressing and molding, drying is performed to obtain a base film; the drying temperature is preferably 20 to 30°C, more preferably 22 to 28°C, and more preferably 25°C; the drying time is preferably 44 to 52 h, more preferably 46 to 50 h, and more preferably 48 h.

[0033] In the present invention, the particle size of the titanium oxide in step (2) is preferably 10 to 30 nm, more preferably 15 to 25 nm, and more preferably 20 to 22 nm; the organic binder preferably includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, and the mass ratio of titanium oxide to organic binder is preferably 1:2.5 to 3.5, more preferably 1:2.7 to 3.3, and more preferably 1:3 to 3.2; the mass fraction of titanium oxide in the titanium oxide sol b is preferably 15 to 25%, more preferably 17 to 23%, and more preferably 20 to 22%.

[0034] In the present invention, the loading method in step (3) is preferably immersion pulling. During immersion pulling, the amount of titania sol b and base film is determined by conventional technical means in the field to ensure that the base film is completely immersed; the number of immersion pulling is preferably 1 to 3 times, more preferably 2 times; the time of each immersion pulling is independently preferably 60 to 90 seconds, further preferably 65 to 85 seconds, and more preferably 70 to 80 seconds.

[0035] In the present invention, after each dipping and pulling in step (3), drying is carried out, and then the next dipping and pulling is carried out, and then drying is carried out again, and the dipping and pulling-drying process is repeated to finally obtain the original film; the drying temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 25°C; the drying time is preferably 44-52h, more preferably 46-50h, and more preferably 48h.

[0036] In the present invention, the sintering atmosphere in step (3) is preferably hydrogen, and the flow rate of hydrogen is preferably 90-120 mL / min, more preferably 100-110 mL / min, and more preferably 105-106 mL / min; the sintering temperature is preferably 1000-1350°C, more preferably 1050-1300°C, and more preferably 1150-1250°C; the sintering time is preferably 6-8 h, more preferably 6.5-7.5 h, and more preferably 6.8-7 h.

[0037] The present invention also provides a carbon-based adsorption electro-catalytic membrane prepared by the method for preparing the carbon-based adsorption electro-catalytic membrane.

[0038] The present invention also provides application of the carbon-based adsorption electrocatalytic membrane in wastewater treatment.

[0039] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0040] Example 1

[0041] Titanium oxide with a particle size of 5 nm, polyvinyl alcohol and water are mixed to obtain a titanium oxide sol a (wherein the mass ratio of titanium oxide to polyvinyl alcohol is 1:4, and the mass fraction of titanium oxide in the titanium oxide sol a is 10%); Titanium oxide with a particle size of 10 nm, polyacrylamide and water are mixed to obtain a titanium oxide sol b (wherein the mass ratio of titanium oxide to polyacrylamide is 1.5:5, and the mass fraction of titanium oxide in the titanium oxide sol b is 15%);

[0042] Under the condition of negative pressure of 0.06MPa, wood activated carbon with a particle size of 50μm was impregnated in titania sol a, the number of impregnations was set to 1 time, the impregnation time was set to 12h, and after the impregnation, it was taken out and dried at 110℃ for 12h under vacuum conditions to obtain Ti4O7 / C powder; Ti4O7 / C powder, titania with a particle size of 50nm, and carbon nanotubes with a length of 10μm were mixed uniformly in a mass ratio of 15:4:1, and then a carbon nanotube with a molecular weight of 3*10 5 Da of polyvinyl alcohol, and mixing them evenly again to obtain a film base material (the mass fraction of the organic binder in the film base material is 6%); the film base material is pressed in a plate mold at 20 MPa, and after pressing and molding, it is dried at 25° C. for 48 hours to obtain a base film;

[0043] The base membrane was immersed in titania sol b and pulled, and the number of immersion and pulling was set to 3 times (each immersion and pulling time was 60s, and after each immersion and pulling, it was dried at 25°C for 48h, and the immersion and pulling-drying process was repeated) to obtain the original membrane; the original membrane was sintered at 1050°C in a hydrogen atmosphere for 6h, and the hydrogen flow rate was set to 100mL / min to obtain the carbon-based adsorption electrocatalytic membrane.

[0044] Example 2

[0045] Titanium oxide with a particle size of 7 nm, polyvinyl alcohol, polyvinylidene fluoride and water are mixed to obtain a titanium oxide sol a (wherein the mass ratio of titanium oxide, polyvinyl alcohol and polyvinylidene fluoride is 1.2:3:2.4, and the mass fraction of titanium oxide in the titanium oxide sol a is 12%); Titanium oxide with a particle size of 20 nm, polyethylene oxide and water are mixed to obtain a titanium oxide sol b (wherein the mass ratio of titanium oxide to polyethylene oxide is 1:2.5, and the mass fraction of titanium oxide in the titanium oxide sol b is 20%);

[0046] Under the condition of negative pressure of 0.04MPa, coconut shell activated carbon with a particle size of 80μm was impregnated in titania sol a, the number of impregnations was set to 4 times, the time of each impregnation was 10h, after each impregnation, it was taken out and dried at 110℃ for 18h under vacuum conditions, and the impregnation-drying process was repeated to finally obtain Ti4O7 / C powder; Ti4O7 / C powder, titania with a particle size of 80nm, and carbon nanotubes with a length of 12μm were mixed uniformly in a mass ratio of 15:4:1, and then a carbon nanotube with a molecular weight of 3*10 5 Da of polyvinyl alcohol, and mixing them evenly again to obtain a film base material (the mass fraction of the organic binder in the film base material is 8%); the film base material is pressed in a plate mold at 25 MPa, and after pressing and molding, it is dried at 25° C. for 48 hours to obtain a base film;

[0047] The base membrane was immersed in titania sol b and pulled, the number of immersion and pulling was set to 1 time, the immersion and pulling time was set to 80s, and after the immersion and pulling was completed, it was dried at 25°C for 48h to obtain the original membrane; the original membrane was sintered at 1150°C in a hydrogen atmosphere for 6h, and the hydrogen flow rate was set to 120mL / min to obtain the carbon-based adsorption electrocatalytic membrane.

[0048] Example 3

[0049] Titanium dioxide with a particle size of 10 nm, paraffin oil, polyacrylamide and water are mixed to obtain a titanium dioxide sol a (wherein the mass ratio of titanium dioxide, paraffin oil and polyacrylamide is 1.4:3.2:3.6, and the mass fraction of titanium dioxide in the titanium dioxide sol a is 14%); Titanium dioxide with a particle size of 30 nm, polyvinyl alcohol and water are mixed to obtain a titanium dioxide sol b (wherein the mass ratio of titanium dioxide and polyacrylamide is 2.5:6.5, and the mass fraction of titanium dioxide in the titanium dioxide sol b is 25%);

[0050] Under the condition of negative pressure of 0.03MPa, wood activated carbon with a particle size of 100μm was impregnated in titania sol a, the number of impregnations was set to 1 time, the impregnation time was set to 8h, and after the impregnation, it was taken out and dried at 110℃ for 24h under vacuum conditions to obtain Ti4O7 / C powder; Ti4O7 / C powder, titania with a particle size of 100nm, and carbon nanotubes with a length of 15μm were mixed uniformly in a mass ratio of 15:4:1, and then a carbon nanotube with a molecular weight of 3*10 5 Da of polyvinyl alcohol, and mixing them evenly again to obtain a film base material (the mass fraction of the organic binder in the film base material is 10%); the film base material is pressed in a tubular mold at 30 MPa, and after pressing and molding, it is dried at 25° C. for 48 hours to obtain a base film;

[0051] The base membrane was dipped and pulled in titania sol b, the number of dips and pulls was set to 1, the time of dips and pulls was set to 90s, after the dips and pulls were completed, it was dried at 25°C for 48h to obtain the original membrane; the original membrane was sintered at 1350°C in a hydrogen atmosphere for 8h, the flow rate of hydrogen was set to 90mL / min, to obtain the carbon-based adsorption electrocatalytic membrane.

[0052] The carbon-based adsorption electrocatalytic membranes prepared in Examples 1 to 3 were used to treat printing and dyeing wastewater with a COD of 44 mg / L, pharmaceutical wastewater with a COD of 52 mg / L, and chemical wastewater with a COD of 48 mg / L, respectively. The treatment conditions were as follows: the applied voltage was 2 V, the carbon-based adsorption electrocatalytic membrane was the anode, the titanium mesh was the cathode, the wastewater volume was 100 mL, the operating pressure was 0.1 MPa, the cycle operation mode was adopted, and the operating time was 60 min. Finally, the wastewater treatment results of the carbon-based adsorption electrocatalytic membranes in Examples 1 to 3 were obtained, as shown in Table 1.

[0053] Table 1 Wastewater treatment results of carbon-based adsorption electrocatalytic membranes in Examples 1 to 3

[0054]

[0055] It can be seen from the above embodiments that the present invention selects titanium oxide, which has advantages in both conductivity and oxygen evolution potential, as a catalytic material, and adopts modified carbon material, titanium oxide and carbon nanotubes as raw materials to prepare an adsorption electrocatalytic membrane, thereby enhancing the conductivity of the carbon material and increasing the electroactive sites. While the carbon nanotubes enhance the adsorption and guidance of the adsorption electrocatalytic membrane, they also serve as connectors to enhance the bonding force between the carbon material and titanium oxide particles, thereby improving the strength of the adsorption electrocatalytic membrane and facilitating the practical application of the adsorption electrocatalytic membrane.

[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-based adsorption electrocatalytic membrane, characterized in that: It includes the following steps: (1) mixing titanium dioxide, an organic binder and water to obtain a titanium dioxide sol a; impregnating activated carbon into the titanium dioxide sol a to obtain Ti4O7 / C powder; Mixing titanium dioxide, Ti4O7 / C powder, carbon nanotubes and an organic binder to obtain a film-based raw material; pressing the film-based raw material to obtain a base film; (2) mixing titanium dioxide, an organic binder and water to obtain a titanium dioxide sol b; (3) loading the titanium oxide sol b on the surface of the base film to obtain an original film; sintering the original film to obtain the carbon-based adsorption electrocatalytic film; There is no order of precedence between step (1) and step (2); In step (1), when preparing the titania sol a, the particle size of the titania is 5-10 nm; when preparing the Ti4O7 / C powder, the particle size of the activated carbon is 50-100 μm; when preparing the membrane-based raw material, the particle size of the titania is 50-100 nm; The particle size of the titanium oxide in step (2) is 10-30 nm.

2. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 1, characterized in that: In step (1), when preparing titania sol a, the organic binder includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, the mass ratio of titania to organic binder is 1:4-5, and the mass fraction of titania in titania sol a is 10-15%.

3. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 1 or 2, characterized in that: In step (1), when preparing Ti4O7 / C powder, the negative pressure value of the immersion is 0.03-0.06 MPa, the number of immersions is 1-5 times, and the time of each immersion is independently 8-12 hours.

4. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 3, characterized in that: In step (1), when preparing the membrane-based raw material, the length of the carbon nanotubes is 10 to 15 μm, the organic binder is polyvinyl alcohol, and the molecular weight of the polyvinyl alcohol is 2*10 5 ~4*10 5 Da; the mass ratio of titanium oxide, Ti4O7 / C powder and carbon nanotubes is 3-5:14-16:0.5-1.5; the mass fraction of the organic binder in the film base material is 5-10%; The pressing pressure in step (1) is 20 to 30 MPa.

5. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 4, characterized in that: The organic binder in step (2) includes one or more of paraffin oil, polyvinyl alcohol, polyacrylamide, polyvinylidene fluoride and polyethylene oxide, the mass ratio of titanium dioxide to the organic binder is 1:2.5-3.5, and the mass fraction of titanium dioxide in the titanium dioxide sol b is 15-25%.

6. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 5, characterized in that: The loading method in step (3) is immersion pulling, the number of immersion pulling is 1 to 3 times, and the time of each immersion pulling is independently 60 to 90 seconds.

7. The method for preparing a carbon-based adsorption electrocatalytic membrane according to claim 6, characterized in that: The sintering atmosphere in step (3) is hydrogen, the flow rate of hydrogen is 90-120 mL / min, the sintering temperature is 1000-1350° C., and the sintering time is 6-8 h.

8. A carbon-based adsorption electrocatalytic membrane prepared by the method for preparing a carbon-based adsorption electrocatalytic membrane according to any one of claims 1 to 7.

9. Use of the carbon-based adsorption electrocatalytic membrane according to claim 8 in wastewater treatment.

Citation Information

Patent Citations

  • Multifunctional hollow fiber electro-catalytic membrane and preparation method thereof

    CN116730442A

  • Carbon membrane having triple functions of adsorption / electrocatalysis / membrane separation, and preparation method of carbon membrane

    CN107051218A

  • Preparation method for Ti407-boron-doped carbon composite anode electrocatalytic membrane

    CN110280230A